Presfektif Islam, Makna dan Tantangan Penguatan Pendiddikan Karakter di Abad 21 - Supardi Widodo; Haryati Haryati; Syarifuddin Ondeng; Munawir Kamaluddin (Jurnal Ilmiah Wahana Pendidikan, 2023)
That education is to prepare individuals or individuals to be able to face this life perfectly, happily, love the motherland, be strong in body, perfect in morals, orderly in thinking, have gentle feelings, proficient in science, help each other to others, improve pen and oral expression and improve his deeds. According to Abrasyi, the main foundation in Islamic character education is faith. Allah gives lessons in Q.S. Luqman/31: 12-19. The advice is explicit, clear and detailed about how Lukman Alhakim educates and directs the child's personality, and maintains his character so that he can face various tests and challenges in life in this world. Strengthening character education in an Islamic perspective is strengthening from the side of faith. The root of faith is the sentence of monotheism which is the basis of a good Islamic personality. Therefore. Strengthening character education is carried out by strengthening faith, namely with an attitude of istiqamah and understanding the dynamics of faith, having faith and being close to the Koran, always being obedient and obedient to Allah, making piety as clothing and carrying out Islam as a whole so that it can achieve degrees of glory with that piety. The challenges of character education in the 21st century are: a character crisis, the emergence of signs of the times that destroy character, mental illness, distortion of moral goodness, transactional culture, and lack of interest in moral and ethical lessons. Therefore strengthening character education is carried out based on religion, namely the Koran. Al-Quran contains many instructions in strengthening character education, namely: the character of worship in Q.S. Al Furqon/25: 63-77, the character of abid, ulil albab, caliph and insan kamil and the growth of work ethic. Efforts to strengthen character education in the family are to increase the role of fathers in children's education. Efforts in education are various efforts to improve the character education system in educational institutions in order to create a school culture and educational institutions that lead to the production of superior human beings and are based on the noble values ​​of Islamic teachings and national culture.